The role of women in the formalisation of housing and placemaking: The case of the Victoria Mxenge housing project - Howard, Ashley (School of Architecture, Planning and Geomatics, 2024)
The formal housing system in Cape Town presents a daunting challenge, with a significant backlog and a growing demand for housing opportunities. Policy challenges persist, including the perception that informal settlements are temporary. Thus, there is a need for a more nuanced approach to housing provision. Furthermore, gender disparities in urban spaces compound issues of well-being, safety, and community-building. Women face obstacles in accessing employment, education, and basic services, limiting their economic independence and social agency. A gendered lens reveals intricate layers of complexity, where disparities in resource access perpetuate the marginalisation of women. Despite constitutional and legislative provisions, women still face obstacles in land ownership and housing access. Thus, there is a need to explore women's inclusion in the formalisation of housing and placemaking to redress the historical and systemic failings of the state. This dissertation examines the multifaceted challenges within informal settlements in Cape Town, South Africa. It delves into three key issues: gender inequalities, the formalisation process of housing, and the need for community-focused placemaking principles. The aim of this study is to investigate the impact of a women-led organisation on the formalisation of housing in informal settlements and how this organisation enables a sense of community through placemaking principles. To these ends, a black feminist lens, radical planning theories and placemaking principles are employed as theoretical frameworks for this study, while the case under study is the Victoria Mxenge Housing Project in Philippi. Methodologically, qualitative research methods (case study method and discourse analysis) are utilised to answer the main and subsidiary research questions. The tools that are used for data collection are interviews and mapping. The results of this study show that women-led organisations have a positive impact on the formalisation of housing and the community in informal settlements. recommends planning interventions and policy changes that emphasise the importance of empowering women through the adoption of gender-sensitive approaches in community initiatives for meaningful, inclusive placemaking. Keywords: women empowerment, inclusive placemaking, access to land and housing, and gender-sensitive planning intervention